1989
DOI: 10.1152/ajpregu.1989.256.1.r161
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoadrenal influence on glucose, FFA, and insulin levels in exercising rats

Abstract: The effects of sympathoadrenal manipulations on the exercise-induced alterations in blood glucose, plasma free fatty acids (FFA), and insulin were investigated in intact and adrenodemedullated rats. Exercise consisted of strenuous swimming against a countercurrent for 15 min. Before, during, and after swimming, blood samples were taken through a permanent heart catheter. Adrenodemedullation (Adm) markedly reduced the exercise-induced increase in both glucose and FFA. This effect was counteracted by intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 7 publications
8
32
0
1
Order By: Relevance
“…Plasma insulin levels were decreased during swimming. The exerciseinduced changes in the blood components were very similar to the changes described for the control animals in previous studies from our laboratory (36,37). Intrahypothalamic infusion of NFFL before exercise increased blood glucose and plasma E concentrations, and failed to influence plasma concentrations Number of rats in brackets.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Plasma insulin levels were decreased during swimming. The exerciseinduced changes in the blood components were very similar to the changes described for the control animals in previous studies from our laboratory (36,37). Intrahypothalamic infusion of NFFL before exercise increased blood glucose and plasma E concentrations, and failed to influence plasma concentrations Number of rats in brackets.…”
Section: Methodssupporting
confidence: 80%
“…of a hypothalamic-adrenalmedullary pathway, leading to an increased release of the adrenal hormone epinephrine. As a consequence, blood glucose levels increased, caused by the stimulatory effect of increased E levels on hepatic glucose production (37,40,43). Hypothalamic administration of NFFL increased plasma corticosterone concentrations in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…The direct effect in vitro occurred within 2 h and is likely to be independent of PPARγ, because PPARγ is weakly expressed in skeletal muscle and, unlike PPAR subtypes α and δ, does not directly regulate the UCP-3 gene [7]. Since other studies have shown that hypoxia and exercise likewise induce immediate increases in both UCP-3 mRNA and plasma NEFA [4,6,8], our findings are in striking agreement with the previously defined hypothesis that an exercise-like component of action, as triggered by inhibition of cell respiration and a reduced cellular energy charge, could contribute to TZD-induced insulin sensitisation (hypothesis outlined in [2]). This interpretation is corroborated in as far as a low cellular energy state induces UCP-3 [4,8], and also by the observed fibre type dependency, since mild inhibition of respiration could result in a more marked ATP deficiency in white than red muscle, according to their different oxidative potentials.…”
Section: Resultsmentioning
confidence: 98%
“…Changes in the concentrations of plasma NEFA were also recorded, because NEFA increase during exercise and also stimulate UCP-3 expression [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, oral glucose tolerance tests or meal tests have indicated that due to an absence of parasympathetic innervation, insulin release did not completely normalize glucose tolerance [5-81. Impaired innervation of transplanted endocrine tissue may not only have its consequences for the parasympathetic control of endocrine function; absence of sympathetic innervation may have its consequences as well. During exercise, enhanced sympathetic activity reduces insulin secretion in rats [9,10], leading to an increase in the portal venous glucagon/ insulin ratio, thus stimulating glycogenolysis and gluconeogenesis [11,12]. Impaired sympathetic control of endocrine pancreatic function in transplanted diabetic rats may therefore lead to impaired recruitment of hepatic glycogen, subsequently leading to an impaired carbohydrate availability for the working muscles.…”
mentioning
confidence: 99%